Características clínico-epidemiológicas de pacientes pediátricos con síndrome nefrítico atendidos en el Hospital Regional de Loreto, 2017-2021 - Díaz Yumbato, Ysrael Hamlet (Universidad Nacional de la Amazonía Peruana, 2023)
The nephritic syndrome is a clinical syndrome that presents as hematuria, hypertension, oliguria and edema, up to 50% of the cases can be subclinical, although it is known that this syndrome continues to have a wide distribution, there is little information in our locality about this syndrome. For this reason, the objective of this work is to determine the clinical-epidemiological characteristics of pediatric patients with nephritic syndrome treated at the Loreto Regional Hospital, 2017-2021. For this reason, a descriptive and cross-sectional study was developed, with 48 pediatric patients as a sample. Concluding that the average age of presentation was 6.25 years, the majority correspond to the male sex (62.5%), 50% of the patients come from rural areas, 10.4% of the patients presented a history of pain in the throat before of hospitalization, 64.6% had a history of skin infections. The most frequent symptoms were edema, hematuria, arterial hypertension with a frequency of 97.9%, followed by fever (77.1%), 39.6% of the patients presented cough, 31.3% presented abdominal pain, 27.1% presented headache, 20.8% % presented diarrhea and no patient presented chills or myalgia.

El síndrome nefrítico es un síndrome clínico que se presenta como hematuria, hipertensión, oliguria y edema, hasta el 50% de los casos pueden ser subclínicos, aunque se sabe que este síndrome continúa teniendo una amplia distribución, existe poca información en nuestra localidad sobre este síndrome. Por esta razón el objetivo de este trabajo es determinar las características clínico-epidemiológicas de pacientes pediátricos con síndrome nefrítico atendidos en el Hospital Regional Loreto, 2017-2021. Por tal motivo se desarrolló un estudio descriptivo y transversal, teniendo como muestra 48 pacientes pediátricos. Concluyendo que la edad promedio de presentación fue de 6,25 años, la mayoría corresponden al sexo masculino (62.5 %), el 50 % de los pacientes proceden de zonas rurales, el 10.4 % de los pacientes presentaron historia de dolor en la garganta antes de la hospitalización, el 64.6 % presentaron historia de infecciones de la piel. Los síntomas más frecuentes fueron edema, hematuria, hipertensión arterial con una frecuencia de 97.9 %, seguido de fiebre (77.1 %), el 39.6 % de los pacientes presentaron tos, el 31.3 % presentaron dolor abdominal, el 27.1 % presentaron cefalea, el 20.8 % presentaron diarrea y ningún paciente presentó escalofríos ni mialgia.
Keywords: Pacientes; Pediatría; Factores epidemiológicos; Signos y síntomas; Síndrome nefrítico; https://purl.org/pe-repo/ocde/ford#3.02.03